Incorporating World Englishes (WE) Into Indonesian Higher Education: Pre-Service Teachers' Perspectives on ELT Pedagogical Implementation - Purba, Hilarius Raditya Priambada; Febria, Desty (JOLLT Journal of Languages and Language Teaching, 2025)
The idea of the new varieties of English produced by many people using English as a lingua franca divides its speakers into three circles; they are inner, outer, and expanding circles. Thus, this study emphasizes the student teachers' perception of the presented phenomena and the practicality of the inclusion of World Englishes as the material taught in the classroom context. The research participants of this study are the student teachers (STs) who the school adapts both national and/ or international curricula as the basis of the teaching and learning process in class. This study employs a qualitative research method. Data triangulation is performed in the study to meet research validity and reliability. In general, STs show a positive attitude toward the concept. Despite their positive view on the concept, there is a lack of effort in practice to introduce students to teaching material that contains WE/ EIL content. It is still a challenge in incorporating this diversity into the classroom in Indonesia, both in national and international schools, as the curriculum and teaching resources remain focused on the inner-circle-country variety. The further pedagogical implementation of ELT is necessary to incorporate a more pluricentric view of English. Moreover, curriculum developers and teacher educators need to advance ELT pedagogy by providing more exposure of varieties to foster enhanced intercultural communication and awareness in language education.